2006
DOI: 10.1080/07420520500545821
|View full text |Cite
|
Sign up to set email alerts
|

Suprachiasmatic Nuclei May Regulate the Rhythm of Leptin Hormone Release in Syrian Hamsters (Mesocricetus Auratus)

Abstract: The suprachiasmatic nuclei (SCN) generate the circadian rhythm of many hormones. The hormone leptin is a metabolic signal that informs the brain about fat and energy stores of the body. We investigated whether the rhythm of leptin hormone release in Syrian hamsters is directly controlled by the SCN. Three experiments were performed: in the first, hamsters were SCN-lesioned; in the second, hamsters were exposed to different feeding regimes; and in the third, hamsters were adrenalectomized and implanted with cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Leptin receptor immunoreactivity has been detected in the suprachiasmatic nuclei of the hypothalamus (SCN), the master circadian clock in mammals (6), and in the hypocretinergic neurones of the lateral hypothalamus, which are implicated in regulating and maintaining sleep/wakefulness states (7,8). Plasma leptin levels show a diurnal rhythm, with a peak around midnight in both rodents and humans (9–11), with the exception of some rodent species, such as hamsters, where peak plasma leptin occur at midday (12).…”
mentioning
confidence: 99%
“…Leptin receptor immunoreactivity has been detected in the suprachiasmatic nuclei of the hypothalamus (SCN), the master circadian clock in mammals (6), and in the hypocretinergic neurones of the lateral hypothalamus, which are implicated in regulating and maintaining sleep/wakefulness states (7,8). Plasma leptin levels show a diurnal rhythm, with a peak around midnight in both rodents and humans (9–11), with the exception of some rodent species, such as hamsters, where peak plasma leptin occur at midday (12).…”
mentioning
confidence: 99%
“…Our animal model is a nocturnal animal, and food intake is more uniformly distributed throughout the day and night (Rowland, 1985). Differences in the phases of leptin rhythms are not due to different preferences in feeding time (Karakas and Gündüz, 2006). Although we did not estimate body fat content, the stability in body weight in response to photoperiods reflected changes in body fat stores and thereby confirmed that circulating leptin does not monitor body fat mass in male Syrian hamsters.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, which employed subcutaneous melatonin implants in pineal-intact hamsters, the marked diurnal variation in serum melatonin titers was abolished as a consequence of elevated daytime levels, but rhythmicity in serum melatonin persisted (Figure 3). It must be stressed that melatonin has receptors in the SCN (Williams et al, 1989), and it is possible that, similar to the rhythm in melatonin release, SCN control of leptin release is mainly stimulatory; thus, removal of this stimulatory SCN control results in decreased leptin levels (Karakas and Gündüz, 2006). Choi and Dallman (1999) reported that in SCN-lesion rats, increased plasma leptin levels are accompanied by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the peak of plasma leptin in hamsters exposed to long or short photoperiods takes place at night, as in other nocturnal rodents like rats and mice (Ahren, 2000 ; Kalsbeek et al, 2001 ; Cuesta et al, 2009 ). Other reports in Syrian hamsters , however, found either hardly rhythmic profile (Horton et al, 2000 ) or rhythmic leptin peaking during daytime (Karakas and Gunduz, 2006 ). The daily rhythm of leptin is thought to be controlled both by the master clock in the SCN and by the adipose clock (Kalsbeek et al, 2001 ; Karakas and Gunduz, 2006 ; Otway et al, 2009 ).…”
Section: Discussionmentioning
confidence: 87%